Southern beech (Nothofagaceae) fossil leaves from the Río Turbio Formation (Eocene-? Oligocene), Santa Cruz Province, Argentina - Panti, Carolina (2019)
Nothofagus sp. cf. N. obliqua, Nothofagus sp. aff. Nothofagus alessandri and Nothofagus magelhaenica are reported for the first time for the Paleogene Río Turbio Formation along with another five fossilspecies: Nothofagus simplicidens, Nothofagus variabilis, Nothofagus lanceolata, Nothofagus subferruginea andNothofagus dicksonii. Around one hundred specimens of fossil leaves were recorded and analysed throughout theunit, but they are fairly more abundant in the upper member of the Río Turbio Formation where they reach 68%of the overall assemblage. The observed increasing trend in Nothofagus abundance throughout the unit coincideswith the beginning of the flora turnover that characterized Patagonian ecosystems from the Late Eocene onwardsand it is in agreement with the marked global cooling trend of the terminal Paleogene.